Does a Lack of Trust Boost Populist Political Parties in Europe? Causal Evidence from Three Methodologies - Jessica Di Cocco; Eugenio Levi; Rama Dasi Mariani; Steven Stillman (CESifo GmbH, 2024)
Existing research has identified several economic and cultural determinants of populist voting. We focus on a related explanation: whether populist leaders are able to capitalize on a sense of distrust between individuals. There is currently limited causal evidence on the relationship between interpersonal trust and support for populist parties, and the underlying mechanisms driving this relationship are not well understood. Using three distinct causal identification strategies, each grounded in different assumptions, we find consistent evidence that a deficit in trust significantly bolsters support for populist political parties throughout Europe. Notably, this influence extends beyond ideological boundaries, encompassing both far-right and far-left populist parties.
Keywords: D72; P00; 330; populism; trust; immigration